2014
DOI: 10.1128/aem.01665-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bacillus subtilis Error Prevention Oxidized Guanine System in Counteracting Hexavalent Chromium-Promoted Oxidative DNA Damage

Abstract: Chromium pollution is potentially detrimental to bacterial soil communities, compromising carbon and nitrogen cycles that are essential for life on earth. It has been proposed that intracellular reduction of hexavalent chromium [Cr(VI)] to trivalent chromium [Cr(III)] may cause bacterial death by a mechanism that involves reactive oxygen species (ROS)-induced DNA damage; the molecular basis of the phenomenon was investigated in this work. Here, we report that Bacillus subtilis cells lacking a functional error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Cr(VI) promotes mutagenesis in eukaryotic and prokaryotic organisms presumably through an indirect mechanism of radical oxygen attack of DNA (2,8). Results described in this work revealed that DNA-protein adducts presumably generated by partially reduced species of hexavalent chromium and processed by components of the SOS system also induced mutagenesis in B. subtilis.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Cr(VI) promotes mutagenesis in eukaryotic and prokaryotic organisms presumably through an indirect mechanism of radical oxygen attack of DNA (2,8). Results described in this work revealed that DNA-protein adducts presumably generated by partially reduced species of hexavalent chromium and processed by components of the SOS system also induced mutagenesis in B. subtilis.…”
Section: Discussionmentioning
confidence: 62%
“…Oxygen radicals generated after reaction of Cr(V) with cellular redox compounds have the ability to affect DNA and to produce distinct types of lesions, including 8-oxoG and AP sites, which are common substrates for the BER pathway (2,9,(52)(53)(54). In support of this notion, recent results revealed a ROS-dependent mechanism of DNA damage that is counteracted by the GO prevention/repair system in B. subtilis (8). The ability of chromate to induce the expression of recA-gfp, recA-lacZ, and uvrA-lacZ fusions revealed that this oxyanion is capable of activating the SOS response in B. subtilis (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations